THE EFFECT OF SERVICE QUALITY AND BRAND IMAGE ON LOYALTY WITH PERCEPTION OF VALUE AS A MEDIATION VARIABLE - Hasby, Rusdy; Irawanto, Dodi Wirawan; Hussein, Ananda Sabil (Universitas Brawijaya, Indonesia, 2018)
This study examines the effect of service quality and brand image on customer loyalty mediated by perceived value. The research surveyed 120 Uber users in DKI Jakarta, through an online questionnaire. Research data were analyzed with Partial Least Square operated through SmartPLS program. The results of the analysis show that perceived value mediates the relationship between service quality and customer loyalty fully, and perceived value mediates the relationship between brand image and customer loyalty partially. Conclusions and implications for the academic and managerial interests of these findings are discussed in this paper.